Regulation of International Trade in Korea under the WTO Mechanism - Lee, Eun Sup (Victoria University of Wellington Law Review, 1998)
This article discusses the development of the trade laws of the Republic of Korea and the important features of the Foreign Trade Act (amended substantially in 1996) and demonstrates the legislative efforts made by the Korean Government to open the domestic market and establish the fair trade system and practices which have been demanded by WTO and major trading partners.